P294 AN ECHOCARDIOGRAPHIC SCORE OF VALVE DISEASE IN PATIENTS WITH CARDIAC AMYLOIDOSIS. (18th May 2022) - Aimo, A; Fabiani, I; Maccarana, A; Fontana, M; Vergaro, G; Chubuchny, V; Pasanisi, E; Petersen, C; Poggianti, E; Giannoni, A; Spini, V; Taddei, C; et al.
Abstract: Background: Cardiac amyloidosis (CA) affects all cardiac structures, including the valves. We summarized the echocardiographic features of valve disease in a score. Methods: From 423 patients undergoing a diagnostic workup for CA we selected 2 samples of 20 patients with amyloid transthyretin (ATTR–) or light–chain (AL–) CA, and selected age– and sex–matched controls. The Amyloid VAlve (AVA) score included 31 items related to the mitral, aortic and tricuspid valves (which can be properly assessed in standard echocardiograms), with a value of 1 for each abnormal item. Results: Patients with ATTR–CA displayed more often a shortened/hidden and retracted posterior mitral valve leaflet (PMVL), thickened mitral chordae tendineae and aortic stenosis than those with AL–CA, and less frequent PMVL calcification than matched controls. Score values were 15.8 (interquartile interval 13.6–17.4) in ATTR–CA, 11.0 (9.3–14.9) in AL–CA, 12.8 (11.1–14.4) in ATTR–CA controls, and 11.0 (9.1–13.0) in AL–CA controls (p = 0.004 for ATTR– vs. AL–CA, 0.009 for ATTR–CA vs. their controls, and 0.461 for AL–CA vs. controls). We compared the AVA and two validated diagnostic scores (IWT and AMYLI). AUC values for the diagnosis of ATTR–CA were 0.782, 0.846 and 0.902, respectively, in patients with ATTR–CA or matched controls, and 0.773, 0.706 and 0.679 in patients with LV hypertrophy (n = 67, 84%) (all non–significant p values). Conclusions: Patients with ATTR–CA have a prominent impairment of mitral valve structure and function, and higher score values. The AVA score is quite effective in identifying patients with ATTR–CA among patients with CA or with unexplained hypertrophy.